1991
DOI: 10.1144/gsl.qjeg.1991.024.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of block size distribution for quarrying

Abstract: The in situ block size and shape parameters of a rock mass with discontinuities are of signifcance for determining whether an existing or virgin quarry is suitable for armourstone production and for designing an appropriate blast pattern. A method for predicting these parameters is presented in this paper, which includes a detailed discontinuity survey technique and computer determination of the blocks dissected by the discontinuities. The applications of the method to simulated discontinuity data and natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 3 publications
0
16
0
2
Order By: Relevance
“…This is definitely a problem in the USA where large stone is repeatedly sold as a by-product of the aggregate and road metal operations. Latham et al (1994) found that even with blasting methods specifically designed for armourstone production, the V80 size was reduced by a factor of six, but with aggregate-type blasting the I180 size was reduced by a factor of 20 or more. Toksrz et al (1971) found that overblasting appears to activate the development of release fractures.…”
Section: Rock Armour Quality Specificationmentioning
confidence: 98%
See 4 more Smart Citations
“…This is definitely a problem in the USA where large stone is repeatedly sold as a by-product of the aggregate and road metal operations. Latham et al (1994) found that even with blasting methods specifically designed for armourstone production, the V80 size was reduced by a factor of six, but with aggregate-type blasting the I180 size was reduced by a factor of 20 or more. Toksrz et al (1971) found that overblasting appears to activate the development of release fractures.…”
Section: Rock Armour Quality Specificationmentioning
confidence: 98%
“…From Figs 1 and 2 the following information is required either during the preliminary desk study or during the quarry evaluation: geological age and formation and miscellaneous geological information developed from published information; regional in situ stress conditions (presence of folds, faults, unloading features and their orientation to quarry face, unloading fractures in quarried stone, rockbursts in quarry floor; also see Hudson & Cooling (1988) and Sbar & Sykes (1973); rock mass conditions (lithological classification of rock type or types present, bedding or strata thickness, variability within beds or strata, stratigraphic log of working face); rock quality (block shape, degree of weathering, perme- Priest (1993) or Wang et al (1991); groundwater conditions (position of groundwater table relative to rock strata of interest, conditions of flow, degree of saturation); block integrity (condition of quarried blocks in regards to the presence of flaws, planes of weakness, blasting fractures, microfractures); and production methods (if blasted, information on blasting methods should include number of rows of blastholes, blasthole diameter and inclination, specific charge or powder factor, type of explosive, bench height, burden distance, spacing distance, stemming material and height). From Fig.…”
Section: Rock Armour Quality Specificationmentioning
confidence: 99%
See 3 more Smart Citations